Effect of Maternal Body Mass Index on N-Terminal Pro B-Type Natriuretic Peptide Levels in the Third Trimester - Saxena, Upma; Yadav, Priyanka; Lachyan, Abhishek; Rani, Anita (American Journal of Perinatology, 2024)
Maternal body mass index (BMI) and cardiac biomarkers, such as N-terminal pro-B-type natriuretic peptide (NT-proBNP), have been subjects of interest in obstetric research due to their potential implications for maternal and fetal health. Previous studies have explored the relationship between maternal BMI and various pregnancy outcomes, but the impact on NT-proBNP levels remains unclear. This study aims to investigate whether maternal BMI influences NT-proBNP levels in the third trimester of pregnancy, which could provide insights into maternal cardiovascular health during late gestation.A total of 234 singleton pregnant women in their third trimester (28–40 weeks) were recruited from Antenatal Care Clinic. Exclusion criteria included preexisting cardiac or renal conditions, hypertension, diabetes mellitus, and other specific medical conditions. Participants were categorized into BMI groups (< 23, 23–24.9, 25–29.9, and ≥30 kg/m2), and their NT-proBNP levels were measured using quantitative enzyme-linked immunosorbent assay kits. Statistical analyses including Spearman correlation, chi-squared test, Kruskal–Wallis test, and regression analysis were performed to assess the association between maternal BMI and NT-proBNP levels.The study population exhibited a range of BMI and NT-proBNP levels within normal ranges. No significant correlation was found between maternal age, parity, and NT-proBNP levels. Similarly, no significant association was observed between maternal BMI and NT-proBNP levels across different BMI categories. Trend analyses showed no consistent relationship between BMI and NT-proBNP levels. Multivariate and univariate regression analyses confirmed the lack of significant association between maternal BMI and NT-proBNP levels.Contrary to expectations, this study found no significant effect of maternal BMI on NT-proBNP levels in the third trimester of pregnancy. These findings suggest that factors other than maternal BMI may predominantly influence NT-proBNP levels during late gestation. Further research is warranted to elucidate the complex interactions between maternal physiology, BMI, and cardiovascular biomarkers during pregnancy.
Keywords: maternal BMI; NT-proBNP; observational study; pregnancy; third trimester